Hubungan Mutu Pelayanan dengan Kepuasan Pasien Peserta BPJS di Rumah Sakit Umum Daerah Yogyakarta - Hastuti, Kurnia Widi; Mudayana, Ahmad Ahid; Nurdila, Arum Putri; Hadiyatma, Deskha (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2017)
Background: The quality of health services in hospitals is strongly influenced by the process of service delivery and the quality factor of physical facilities, drugs and medical devices of human resources. The purpose of this study is to look at the relationship between the quality of care with patient satisfaction BPJS participants in District hospital DIY. Method: This research was quantitative research, with cross sectional design. It was conducted in Sleman district Hospital and Bantul District Hospital. The number of samples in this research was 203 patients on BPJS. Analysis of the data used in the bivariate analysis using chi-square test, and multivariate analysis using linear regression analysis. Results: The results showed p-value of all the variables is smaller than the value Î± (0.000<0.05), so it can be concluded that Ha Ho accepted and rejected. The order of the strength of the relationship is the largest to the smallest empathy (OR=0.342), tangibility (OR=0.280), reliability (OR=0.266) and assurance (OR=0.230) as well as variable responsiveness has a p-value 0.215. Conclusion: There were no relationship between tangibility, reliability, responsiveness, assurance, empathy and patient satisfaction with service quality. Variable responsiveness has no effect on satisfaction